Saving the American Dream? Education Policies in Spatial General Equilibrium - Eckert, Fabian; Kleineberg, Tatjana (World Bank, Washington, DC, 2021)
Children's education and economic opportunities differ substantially across US neighborhoods. This paper develops and estimates a spatial equilibrium model that links children's education outcomes to their childhood location. Two endogenous factors determine education choices in each location: local education quality and local labor market access. This paper estimates the model with US county-level data and studies the effects of a school funding equalization on education outcomes and social mobility. The reform's direct effects improve education outcomes among children from low-skill families. However, the effects are weaker in spatial general equilibrium because average returns to education decline and residential and educational choices of low-skill families shift them toward locations with lower education quality.